(untitled) (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To know about the various pathogens causing infection in Orthopaedic implant surgeries and their antibiotic sensitivities. Methods: This prospective study was conducted in Department of Orthopaedics, Khyber teaching Hospital, Peshawar, from January 2015 to December 2015. All patients having close fractures of long bones including humerus, radius/ulna, femur and tibia requiring open reduction and internal fixation ORIF were included. Patients data was noted on a preformed proforma. Patients were followed up to 6 months. Results: 30 patients out of 650 developed Surgical site infection were selected. 23 were male and 7 were female patients. Age range was from 5-75 years. Staph Aureus including Methicillin resistant Staph Aureus MRSA was most common cultured organism, followed by E Coli and pseudomonas. 23 cases yielded single organism, 5 cases yielded 2 organisms, 1 case yielded 3 organisms. There was no organism growth in one case. Conclusion: Staph aureus including MRSA is the main cause of surgical site infection in orthopedics implant surgery. Other bacteria like E. Coli may cause surgical site infection. Antibiotics should be prescribed according to culture and sensitivity reports.